2021
DOI: 10.3390/molecules26020412
|View full text |Cite
|
Sign up to set email alerts
|

A New CDK2 Inhibitor with 3-Hydrazonoindolin-2-One Scaffold Endowed with Anti-Breast Cancer Activity: Design, Synthesis, Biological Evaluation, and In Silico Insights

Abstract: Background: Cyclin-dependent kinases (CDKs) regulate mammalian cell cycle progression and RNA transcription. Based on the structural analysis of previously reported CDK2 inhibitors, a new compound with 3-hydrazonoindolin-2-one scaffold (HI 5) was well designed, synthesized, and biologically evaluated as a promising anti-breast cancer hit compound. Methods: The potential anti-cancerous effect of HI 5 was evaluated using cytotoxicity assay, flow cytometric analysis of apoptosis and cell cycle distribution, ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Cell cycle imbalance is common in different tumors ( Chen T. et al, 2021 ). Cell-dependent kinase (CDK) is involved in many tumors related biological processes, such as cell cycle, immune checkpoint ( Hume et al, 2020 ), RNA transcription ( Al-Sanea et al, 2021 ), cell proliferation ( Liu J. et al, 2021 ). Recently, there have been studies on CDK4 ( Pandey et al, 2021 ) and CDK6 ( Pandey et al, 2021 ), but the mechanism of CDK2 ( El-Sattar et al, 2021 ) in cancer is relatively lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle imbalance is common in different tumors ( Chen T. et al, 2021 ). Cell-dependent kinase (CDK) is involved in many tumors related biological processes, such as cell cycle, immune checkpoint ( Hume et al, 2020 ), RNA transcription ( Al-Sanea et al, 2021 ), cell proliferation ( Liu J. et al, 2021 ). Recently, there have been studies on CDK4 ( Pandey et al, 2021 ) and CDK6 ( Pandey et al, 2021 ), but the mechanism of CDK2 ( El-Sattar et al, 2021 ) in cancer is relatively lacking.…”
Section: Discussionmentioning
confidence: 99%
“…A recent in vitro study demonstrated a new CDK2 inhibitor with 3-hydrazonoindolin-2-one scaffold, called HI 5 ( Figure 10 ). This inhibitor induced intrinsic apoptosis in human breast cancer cell line MCF-2 [ 117 ].…”
Section: Development Of Selective Cdk Inhibitorsmentioning
confidence: 99%
“…Isatin derivatives have the potential to modulate multiple biological targets, such as histone deacetylase, β-carbonic anhydrase, tyrosine kinase, phosphodiesterase 4B, and tubulin, changing the expression of particular apoptosis-related genes and eventually causing apoptosis [ 19 ]. Furthermore, several potent antitumor agents, such as semaxanib and sunitinib, contain an isatin scaffold ( Figure 1 ), demonstrating that isatin is an effective moiety for the development of novel anticancer agents [ 20 ]. On the other hand, purine-containing compounds such as I and II ( Figure 1 ) were also found to be good anticancer agents due to their multitarget effects, including the inhibition of the activity of CDKs, EGFR, VEGFR2, HDAC, mTOR, MAPK and MNK [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%